2014
DOI: 10.1002/poc.3341
|View full text |Cite
|
Sign up to set email alerts
|

An attempt of molecular design and synthesis of 3,4′/4,3′-disubstituted benzylideneanilines with specified UV-Vis absorption maximum wavelength

Abstract: Thirty‐one samples of 3,4′/4,3′‐disubstituted benzylideneanilines (XBAY) with specified UV–Vis absorption maximum wavelength (λmax) were designed and synthesized by applying the equation (Eqn ) which was abstracted from the UV–Vis absorption maximum wavelength energy (νmax = 1/λmax) of 4,4′‐disubstituted benzylideneanilines. Then, the UV–Vis data (λmax) of the designed compounds were measured in anhydrous ethanol. The predicted UV–Vis data of designed compounds are in agreement with the experimental ones, in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Then, the designed compounds were synthesized, and their UV absorption spectra were measured in anhydrous ethanol. Wang's results showed that the predicted λ max values of the designed compounds were in agreement with the experimental ones. Recently, Wang further quantified the ν max (ie, ν max = 1/λ max ) of disubstituted/multi‐substituted N‐(benzylidene)‐anilines XArCH=NArY (abbreviated XBAY) and proposed Equation to express the ν max change regularity for 167 samples of XBAY that contain 1 to 4 substituents.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Then, the designed compounds were synthesized, and their UV absorption spectra were measured in anhydrous ethanol. Wang's results showed that the predicted λ max values of the designed compounds were in agreement with the experimental ones. Recently, Wang further quantified the ν max (ie, ν max = 1/λ max ) of disubstituted/multi‐substituted N‐(benzylidene)‐anilines XArCH=NArY (abbreviated XBAY) and proposed Equation to express the ν max change regularity for 167 samples of XBAY that contain 1 to 4 substituents.…”
Section: Introductionsupporting
confidence: 64%
“…The compounds involved are the following: 4,4′‐disubstituted N‐(benzylidene)‐anilines p‐XArCH=NArY‐p, symmetrical Schiff bases derived from 1,4‐phenylenediamines p‐XArCH=NArN=CHArX‐p, extended benzylidene anilines p‐XArCH=NArCH=CHArY‐p, N‐(4‐substituted bezylidene) cyclohexylamines p‐XArCH=NC 6 H 11 , N‐(phenyl‐ethylene)‐anilines XArC(CH3)=NArY, and N‐phenyl‐α‐phenylnitrones XArCH=N(O)ArY . On the bases of Cao's works, Wang explored a molecular design and obtained 31 samples of 3,4′/4,3′‐disubstituted N‐(benzylidene)‐anilines 3/4‐XArCH=NArY‐4′/3′ with specified λ max . Then, the designed compounds were synthesized, and their UV absorption spectra were measured in anhydrous ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…These studies of substituent effects on the ν max of aryl‐Schiff bases show that not only the excited‐state substituent parameter σccex, but also Hammett constant σ were employed in the quantitative correlations of the ν max . Wang even made an attempt of molecular design and synthesis of 3,4’/4,3’‐disubstituted benzylidene anilines with specified λ max , on the basis of Chen's report, in which the predicted λ max values are in agreement with the experimental ones for these designed compounds.…”
Section: Introductionmentioning
confidence: 92%
“…For this purpose, two series of compounds, XPEAYs and XPNYs were synthesized, next, their wavelength of absorption maximum λ max (nm) in the UV spectra were measured, and then, the correlations between the ν max , (cm ‐1 , ν max =1/λ max ) and the substituent effects of X and Y were carried out for the compounds XPEAYs and XPNYs, also the different effect of substituents on the ν max of the three kinds of compounds XBAY, XPEAY and XPNY were investigated in this work. Maybe it can provide us with a valuable reference for designing and using these three kinds of compounds as optical materials …”
Section: Introductionmentioning
confidence: 99%
“…The polymers and coordination compounds in the benzylideneaniline class (with π conjugate systems) are important optical functional compounds and have been applied extensively in the fields of liquid crystal materials [22]. Thus, we calculated and tested 34 molecular descriptors, of which 25 topological indices and 12 Van der Waals parameters.…”
Section: Introductionmentioning
confidence: 99%